Avaliação das microestruturas de solidificação e propriedades de aplicação de ligas monotéticas Al-Bi, Al-Bi-Cu e Al-Bi-Zn - Reyes, Rodrigo André Valenzuela (Universidade Federal de São Carlos, 2021)
Monotectic Al-based ternary alloys can result in a good combination of wear resistance and mechanical strength. While the soft self-lubricating elements contribute to an appropriate wear resistance, modification with third elements can increase the load-bearing capacity. The control of thermal solidification parameters, under conditions of transient heat flow, may provide an optimized distribution of the minority soft phase of Bismuth (Bi) incorporated in an Al-rich matrix. In the present study, Al-Bi, Al-Bi-Zn and Al-Bi-Cu alloys were generated by directional solidification technique, having the microstructures characterized and dimensioned based on the cooling rates (Ṫ). The main objective is to evaluate the influences of the addition of elements - typical hardeners in Al alloys: 3wt.% zinc (Zn) and 3wt.% copper (Cu) - in the microstructures (through Bi spacing, λBi), tensile properties and wear resistances of the monotectic Al-3,2 wt.% Bi alloy. These additions contribute to the development of light and more resistant alloys in new designs of sliding bearings, whose demands are increasing. It is shown that the addition of Cu promotes 50% of microstructural refining (from 88 μm to 44 μm, for Ṫ = 1 ° C/s), almost doubles the wear resistance (average worn volume, V, reduced from 0.43 mm3 to 0.27 mm3 for 60 minutes of testing) and more than doubles the ultimate tensile strength (from 70 MPa to 165 MPa) with a decrease in elongation-to-fracture (from 40% to 25%) compared to the Al-3.2 wt.% Bi alloy. Regarding to the addition of Zn, although there is some microstructural refinement (40% for Ṫ = 1 ° C/s), little contribution was observed in the application properties. Hall-Petch equations correlating the tensile properties with the interphase spacing (λBi) have been proposed, as well as relationships between the V as a function of both λBi and test time (t).
Evaluation of as-solidified microstructures and application properties of Al-Bi, Al-Bi-Cu and Al-Bi-Zn monotectic alloys
Keywords: Solidificação; Desgaste; Ligas ternárias; Ligas monotéticas; Al-Bi; Al-Bi-Zn; Al-Bi-Cu; Propriedades mecânicas; Solidification; Wear; Ternary alloys; Monotectic alloys; Mechanical properties; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA